2020
DOI: 10.1080/07391102.2020.1760137
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of potential multi-target-directed ligands by targeting host-specific SARS-CoV-2 structurally conserved main protease

Abstract: 2020): Discovery of potential multi-target-directed ligands by targeting host-specific SARS-CoV-2 structurally conserved main protease, Journal of Biomolecular Structure and Dynamics, ABSTRACT Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has resulted in the current COVID-19 pandemic. Worldwide this disease has infected over 2.5 million individuals with a mortality rate ranging from 5 to 10%. There are several efforts going on in the drug discovery to control the SARS-CoV-2 viral infec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
275
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(279 citation statements)
references
References 47 publications
4
275
0
Order By: Relevance
“…The fusion of coronavirus requires proteolytic priming of its spike protein in the endosomal system. Besides, inhibition of lysosomal proteases had been hypothesised to prevent coronavirus fusion as shown in a study using mouse hepatitis virus (MHV) a safe model of coronavirus (de Haan et al, 2004;Hasan et al, 2020;Joshi et al, 2020). Various studies had been reported using computational approaches in investigating putative compounds that could be repurposed or repositioned as drugs against coronavirus (Aanouz et al, 2020;Elfiky & Azzam, 2020;Enayatkhani et al, 2020;Enmozhi et al, 2020;Gupta et al, 2020;Khan et al, 2020b;Sarma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The fusion of coronavirus requires proteolytic priming of its spike protein in the endosomal system. Besides, inhibition of lysosomal proteases had been hypothesised to prevent coronavirus fusion as shown in a study using mouse hepatitis virus (MHV) a safe model of coronavirus (de Haan et al, 2004;Hasan et al, 2020;Joshi et al, 2020). Various studies had been reported using computational approaches in investigating putative compounds that could be repurposed or repositioned as drugs against coronavirus (Aanouz et al, 2020;Elfiky & Azzam, 2020;Enayatkhani et al, 2020;Enmozhi et al, 2020;Gupta et al, 2020;Khan et al, 2020b;Sarma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The main active ingredient of turmeric, Curcumin has been widely studied to have a broad spectrum of medicinal value ranging from anti-cancerous, anti-inflammatory and an anti-amyloidogenic activity (Bhagya & Raveendra, 2017). Several computational studies related to drug or vaccine development against SARS-CoV-2 is recently published (Aanouz et al, 2020;Gupta et al, 2020;Joshi et al, 2020;Muralidharan et al, 2020;Sarma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 also called 'severe acute respiratory syndrome coronavirus 2' abbreviated SARS-CoV-2 was recognized to be the causative of atypical pneumonia (Joshi, 2020;Pant et al, 2020) outbreak in Wuhan, China (Hasan, 2020;S. A. Khan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%